Let the Writer Beware! - a Look at Aspects of the EU Legislation Concerning Instructional Texts - Kastberg, Peter (Language at Work - Bridging Theory and Practice, 2007)
We have probably all heard the story of the person who supposedly put a wet dog into the microwave oven to let it dry or the story of the person who drank coffee from a plastic cup and got severely burned, or the one in which a jogger stumbles and falls in the too long shoe laces of his / her sneakers. Whether or not stories like these are urban legends is hard to determine with any certainty. But judging from the ever increasing volume of the instruction manuals accompanying, for instance, our household appliances and other end user products there could be some truth to them.